You are on page 1of 79

On the WZ Method

Ira M. Gessel

Department of Mathematics
Brandeis University

Waterloo Workshop in Computer Algebra


Wilfrid Laurier University
May 28, 2011

In Honor of Herbert Wilf’s 80th Birthday


The WZ (Wilf-Zeilberger) method

The way the WZ method is usually described:


We have two functions f and g satisfying the WZ equation

f (i, j + 1) − f (i, j) = g(i + 1, j) − g(i, j) (WZ)


The WZ (Wilf-Zeilberger) method

The way the WZ method is usually described:


We have two functions f and g satisfying the WZ equation

f (i, j + 1) − f (i, j) = g(i + 1, j) − g(i, j) (WZ)

If we sum on i the right side telescopes, so


N
X N
X
f (i, j + 1) − f (i, j) = g(N + 1, j) − g(0, j).
i=0 i=0
The WZ (Wilf-Zeilberger) method

The way the WZ method is usually described:


We have two functions f and g satisfying the WZ equation

f (i, j + 1) − f (i, j) = g(i + 1, j) − g(i, j) (WZ)

If we sum on i the right side telescopes, so


N
X N
X
f (i, j + 1) − f (i, j) = g(N + 1, j) − g(0, j).
i=0 i=0
P
0 then N
If g(N + 1, j) = g(0, j) =P i=0 f (i, j + 1) is independent
of j so we can evaluate i f (i, j).
The WZ (Wilf-Zeilberger) method

The way the WZ method is usually described:


We have two functions f and g satisfying the WZ equation

f (i, j + 1) − f (i, j) = g(i + 1, j) − g(i, j) (WZ)

If we sum on i the right side telescopes, so


N
X N
X
f (i, j + 1) − f (i, j) = g(N + 1, j) − g(0, j).
i=0 i=0
P
0 then N
If g(N + 1, j) = g(0, j) =P i=0 f (i, j + 1) is independent
of j so we can evaluate i f (i, j).
Note: we might want to take N = ∞.
An example—Vandermonde’s theorem

Let’s use the WZ method to prove the Chu-Vandermonde


theorem:
Xr     
p q p+q
=
i r −i r
i=0
An example—Vandermonde’s theorem

Let’s use the WZ method to prove the Chu-Vandermonde


theorem:
Xr     
p q p+q
=
i r −i r
i=0

It’s convenient to replace the upper limit of summation with ∞.


We divide the left side by the right side to get a sum which is
independent of the parameters:

X    
p q p+q
ti = 1, where ti = .
i r −i r
i=0

To apply the WZ method, we need a second parameter j. But


we have three parameters, p, q, and r . Which one should we
take?
Let’s
P∞ try taking p to be j. So our identity becomes
i=0 f (i, j) = 1, where
   
j q j +q
f (i, j) = .
i r −i r
Let’s
P∞ try taking p to be j. So our identity becomes
i=0 f (i, j) = 1, where
   
j q j +q
f (i, j) = .
i r −i r

We would like to find a WZ-mate for f : a solution of the WZ


equation f (i, j + 1) − f (i, j) = g(i + 1, j) − g(i, j).
Let’s
P∞ try taking p to be j. So our identity becomes
i=0 f (i, j) = 1, where
   
j q j +q
f (i, j) = .
i r −i r

We would like to find a WZ-mate for f : a solution of the WZ


equation f (i, j + 1) − f (i, j) = g(i + 1, j) − g(i, j). We can do this
using Gosper’s algorithm, which gives

i (q − r + i)
g(i, j) = f (i, j)
(i − 1 − j)(j + 1 + q)
   
i +q−r j q j +q
=− .
j +q+1 i −1 r −i r
Let’s
P∞ try taking p to be j. So our identity becomes
i=0 f (i, j) = 1, where
   
j q j +q
f (i, j) = .
i r −i r

We would like to find a WZ-mate for f : a solution of the WZ


equation f (i, j + 1) − f (i, j) = g(i + 1, j) − g(i, j). We can do this
using Gosper’s algorithm, which gives

i (q − r + i)
g(i, j) = f (i, j)
(i − 1 − j)(j + 1 + q)
   
i +q−r j q j +q
=− .
j +q+1 i −1 r −i r

Since g(0, j) = 0 and g(i, j) = 0 for i > j + 1, we have



X 
f (i, j + 1) − f (i, j) = 0.
i=0
So X
f (i, j)
i

is independent of j and is therefore equal to


X
f (i, 0) = 1
i

(at least as long as j is a nonnegative integer).


What if we take r to be j? So
   
p q p+q
f (i, j) = .
i j −i j

We apply Gosper’s algorithm and it is again successful: we find


the WZ-mate
i (q − j + i)
g(i, j) = f (i, j)
(i − 1 − j)(p + q − j)
   
j p+q−j −1 p+q
=− .
i −1 p−i p
We find that any way of making the parameters linear functions
of j works.
We find that any way of making the parameters linear functions
of j works.
For example, if we replace i → i + j, p → p + j, q → q − j, so
that    
p+j q−j p+q+j
f (i, j) = .
i +j r −i −j r
then Gosper’s algorithm finds a WZ-mate for f ,

q−r +i
g(i, j) = f (i, j).
q−j
So we have many (infinitely many, in fact) slightly different WZ
proofs of Vandermonde’s theorem.
So we have many (infinitely many, in fact) slightly different WZ
proofs of Vandermonde’s theorem.
I Why does Gosper’s algorithm always work?
So we have many (infinitely many, in fact) slightly different WZ
proofs of Vandermonde’s theorem.
I Why does Gosper’s algorithm always work?
I Why should we care?
Path Invariance

(Gosper, Kadell, Zeilberger)


Another way to look at WZ pairs: We consider a grid graph with
a weight function defined on every directed edge with the
following property:
I For all vertices A and B, all paths from A to B have the same
weight. (path invariance)
1 2 2

1 1 1 1
1 2 2

2 2 0 1
1 4 1
This property is equivalent to the existence of a potential
function defined on the vertices: the weight of an edge is the
difference in the potential of its endpoints:

3 1 4 2 6 2 8

1 1 1 1
2 1 3 2 5 2 7

2 2 0 1
1 1 4 5 1 6
0
Some observations

I To check that a weighted grid graph has the path invariance


property, it is sufficient to check it on each rectangle:

a d a+b=c+d

c
Some observations

I We can add arbitrary other edges to the graph, and they will
have uniquely determined weights that satisfy the path invari-
ance property.

1 2 2

1 1 1 1
1 2 2

2 2 0 1
1 4 1
Some observations

I The weights of a directed edge and its reversal are negatives


of each other.
In particular, from one path-invariant weighted grid graph, we
can get another by taking a different grid on the same set of
points:
In particular, from one path-invariant weighted grid graph, we
can get another by taking a different grid on the same set of
points:
In particular, from one path-invariant weighted grid graph, we
can get another by taking a different grid on the same set of
points:
In particular, from one path-invariant weighted grid graph, we
can get another by taking a different grid on the same set of
points:
Suppose that we have a a path-invariant weighted grid graph,
where the vertices are in Z × Z. Let f (i, j) be the weight on the
edge from (i, j) to (i + 1, j) and let g(i, j) be the weight on the
edge from (i, j) to (i, j + 1):

f (i, j + 1)

g(i, j) g(i + 1, j)

(i, j)
f (i, j)
Suppose that we have a a path-invariant weighted grid graph,
where the vertices are in Z × Z. Let f (i, j) be the weight on the
edge from (i, j) to (i + 1, j) and let g(i, j) be the weight on the
edge from (i, j) to (i, j + 1):

f (i, j + 1)

g(i, j) g(i + 1, j)

(i, j)
f (i, j)

The path invariance property is

f (i, j) + g(i + 1, j) = g(i, j) + f (i, j + 1)

This is the same as the WZ identity.


We can think of our previous application of the WZ identity in
terms of path invariance: We rewrite the identity
N
X N
X
f (i, j + 1) − f (i, j) = g(N + 1, j) − g(0, j).
i=0 i=0

as
N
X N
X
g(0, j) + f (i, j + 1) = f (i, j) + g(N + 1, j).
i=0 i=0

This comes from path invariance along these paths:

(0, j + 1) (N + 1, j + 1)

(0, j) (N + 1, j)
path invariance vs. telescoping series viewpoint

I Using path invariance, can find other kinds of identities by


summing along different paths.
path invariance vs. telescoping series viewpoint

I Using path invariance, can find other kinds of identities by


summing along different paths.
I Rather than proving the telescoping formula
N
X N
X
f (i, j + 1) − f (i, j) = 0,
i=0 i=0

we can prove directly that


N
X
f (i, j) = 1.
i=0

using the following two paths:


N
!
f (i, j)
i=0
(0, j) (N + 1, j)

0 0

(0, 0) 1 (1, 0) 0 (N + 1, 0)
Another important example of path invariance:

(0, M )

M
X −1
g(0, j)
j=0

(0, 0) M
X −1
(M, 0)
f (i, 0)
i=0

If the weight of the green connecting path goes to 0 as M → ∞


then
X∞ ∞
X
f (i, 0) = g(0, j).
i=0 j=0
Change of Variables

Path invariance allows us to assign a weight to any step,


thereby giving us change of variables formulas for WZ pairs.
Change of Variables

Path invariance allows us to assign a weight to any step,


thereby giving us change of variables formulas for WZ pairs.
Suppose we have a WZ pair (f (i, j), g(i, j)). We take the steps
(1, 0) and (1, 1).
The weight of an edge from (i, j) to (i + 1, j) is f (i, j).
Change of Variables

Path invariance allows us to assign a weight to any step,


thereby giving us change of variables formulas for WZ pairs.
Suppose we have a WZ pair (f (i, j), g(i, j)). We take the steps
(1, 0) and (1, 1).
The weight of an edge from (i, j) to (i + 1, j) is f (i, j).
Let h(i, j) be the weight of a step from (i, j) to (i + 1, j + 1), so

h(i, j) = f (i, j) + g(i + 1, j) = g(i, j) + f (i, j + 1).


Then we have the path invariance formula

h(i, j) + f (i + 1, j + 1) = f (i, j) + h(i + 1, j) (∗)

f (i + 1, j + 1) (i + 2, j + 1)

h(i, j) h(i + 1, j)

(i, j) f (i, j)

To get a WZ pair we must represent the values of f and h in the


coordinates (1, 0) and (1, 1).
Then we have the path invariance formula

h(i, j) + f (i + 1, j + 1) = f (i, j) + h(i + 1, j) (∗)

f (i + 1, j + 1) (i + 2, j + 1)

h(i, j) h(i + 1, j)

(i, j) f (i, j)

To get a WZ pair we must represent the values of f and h in the


coordinates (1, 0) and (1, 1).
Since i(1, 0) + j(1, 1) = (i + j, j), we set F (i, j) = f (i + j, j) and
H(i, j) = h(i + j, j). Then replacing i with i + j in (∗) gives

H(i, j) + F (i, j + 1) = F (i, j) + H(i + 1, j)



so F (i, j), H(i, j) is a WZ pair.
Path invariance in several variables

In n variables we may define a WZ n-tuple to be an n-tuple



f1 (i1 , . . . , in ), . . . , fn (i1 , . . . , in )

such that for j 6= k , the pair (fj , fk ) is a WZ-pair with respect to


the variables ij and ik .
Path invariance in several variables

In n variables we may define a WZ n-tuple to be an n-tuple



f1 (i1 , . . . , in ), . . . , fn (i1 , . . . , in )

such that for j 6= k , the pair (fj , fk ) is a WZ-pair with respect to


the variables ij and ik .
This implies that if we put a weight of fj (i1 , . . . , in ) on the edge
from (i1 , . . . , in ) to the adjacent point (i1 , . . . , ij + 1, . . . , in ) then
we get a path-invariant grid graph in Zn (or Cn or Rn ).
Path invariance in several variables

In n variables we may define a WZ n-tuple to be an n-tuple



f1 (i1 , . . . , in ), . . . , fn (i1 , . . . , in )

such that for j 6= k , the pair (fj , fk ) is a WZ-pair with respect to


the variables ij and ik .
This implies that if we put a weight of fj (i1 , . . . , in ) on the edge
from (i1 , . . . , in ) to the adjacent point (i1 , . . . , ij + 1, . . . , in ) then
we get a path-invariant grid graph in Zn (or Cn or Rn ).

Since there are n2 conditions, it would seem to be difficult to
satisfy them all.
Path invariance in several variables

In n variables we may define a WZ n-tuple to be an n-tuple



f1 (i1 , . . . , in ), . . . , fn (i1 , . . . , in )

such that for j 6= k , the pair (fj , fk ) is a WZ-pair with respect to


the variables ij and ik .
This implies that if we put a weight of fj (i1 , . . . , in ) on the edge
from (i1 , . . . , in ) to the adjacent point (i1 , . . . , ij + 1, . . . , in ) then
we get a path-invariant grid graph in Zn (or Cn or Rn ).

Since there are n2 conditions, it would seem to be difficult to
satisfy them all. But it’s really not so hard:
Lemma. Suppose that for j = 2, . . . , n, (f1 , fj ) is a WZ pair with
respect to the variables i1 and ij . Then (f1 , . . . , fn ) is a WZ
n-tuple in the variables i1 , . . . , in .
WZ forms

Zeilberger introduced WZ forms (in Closed Form (Pun


Intended!) ) as a way to associate the variables to the functions
in a WZ n-tuple. To the WZ n-tuple (f1 , . . . , fn ) we associate the
WZ form
X n
fj (i1 , . . . , in ) δij ,
j=1

by analogy with differential forms, where δij is a “formal


symbol". So summing a WZ form along a path is analogous to
integrating a differential form along a path.
Going back to the Chu-Vandermonde theorem,
r  
X   
p q p+q
= ,
i r −i r
i=0

by applying Gosper’s algorithm we can find a corresponding


WZ form in four variables, i, p, q, and r :
  
p q

i r −i i (q − r + i)
ωV =   δi − δp
p+q (p + 1 − i)(p + 1 + q)
r

i i (q − r + i)
+ δq − δr
p+q+1 (r − i + 1)(p + q − r )
As in our change of variables formula, we can get all the
different WZ pairs (or more generally, WZ forms) corresponding
to parametrizations of Vandermonde’s theorem by taking
different basis steps and using ωV to evaluate the weights of
these steps.
As in our change of variables formula, we can get all the
different WZ pairs (or more generally, WZ forms) corresponding
to parametrizations of Vandermonde’s theorem by taking
different basis steps and using ωV to evaluate the weights of
these steps.
But we don’t need to find these WZ pairs; all the results that we
might have found from them we can get directly from path
invariance.
The central fact developed is that identities are both
inexhaustible and unpredictable; the age-old dream of putting
order in this chaos is doomed to failure.
John Riordan, Combinatorial Identities
The central fact developed is that identities are both
inexhaustible and unpredictable; the age-old dream of putting
order in this chaos is doomed to failure.
John Riordan, Combinatorial Identities

WZ forms bring order to this chaos.


What WZ forms are there?

All WZ forms are associated with one of four standard


hypergeometric series summation formulas:
What WZ forms are there?

All WZ forms are associated with one of four standard


hypergeometric series summation formulas:

I The binomial theorem


What WZ forms are there?

All WZ forms are associated with one of four standard


hypergeometric series summation formulas:

I The binomial theorem


I the Chu-Vandermonde theorem (Gauss’s theorem)
What WZ forms are there?

All WZ forms are associated with one of four standard


hypergeometric series summation formulas:

I The binomial theorem


I the Chu-Vandermonde theorem (Gauss’s theorem)
I the Pfaff-Saalschütz theorem
What WZ forms are there?

All WZ forms are associated with one of four standard


hypergeometric series summation formulas:

I The binomial theorem


I the Chu-Vandermonde theorem (Gauss’s theorem)
I the Pfaff-Saalschütz theorem
I Dougall’s very-well-poised 7 F6 summation theorem
What WZ forms are there?

All1 WZ forms are associated with one of four standard


hypergeometric series summation formulas:

I The binomial theorem


I the Chu-Vandermonde theorem (Gauss’s theorem)
I the Pfaff-Saalschütz theorem
I Dougall’s very-well-poised 7 F6 summation theorem

1
almost
Shifting and shadowing

In addition to change of variables, which comes from path


independence, there are two other simple operations on WZ
forms that give forms we will consider to be equivalent.
It is convenient to assume that all of our functions are “closed
form" or “proper hypergeometric terms" or gamma quotients: in
two variables (i and j) for simplicity, we want each to be of the
form
Γ(a1 i + b1 j + u1 ) · · · Γ(ak i + bk j + uk ) i j
f (i, j) = zw
Γ(c1 i + d1 j + v1 ) · · · Γ(cl i + dl j + vl )

where the an , bn , cn , and dn are integers, and the un , vn , z, and


w are complex numbers. It is also convenient to allow i and j to
be complex numbers, so that f is a meromorphic function.
(Similarly for more than two variables.)
I Shifting
We replace a variable i in a WZ form with i + c for some c ∈ C.
I Shifting
We replace a variable i in a WZ form with i + c for some c ∈ C.
I Shadowing
We can multiply a WZ form by any periodic function with period
1 in each variable. In particular, we can take as our multiplier
π
(−1)i Γ(i)Γ(1 − i) = (−1)i .
sin πi
So we can replace 1/Γ(i) with (−1)i Γ(1 − i) or vice versa.
I Shifting
We replace a variable i in a WZ form with i + c for some c ∈ C.
I Shadowing
We can multiply a WZ form by any periodic function with period
1 in each variable. In particular, we can take as our multiplier
π
(−1)i Γ(i)Γ(1 − i) = (−1)i .
sin πi
So we can replace 1/Γ(i) with (−1)i Γ(1 − i) or vice versa.
This allows us to get rid of inconvenient zeros or poles.
Rising factorials

It is convenient to use the notation for rising factorials,

(a)k = a (a + 1) · · · (a + k − 1)
Γ(a + k )
= .
Γ(a)

So, for example,

n! = (1)n
(2n)! = 22n ( 12 )n (1)n
n + 1 = (2)n /(1)n
A zeta function example

A well-known formula for ζ(2) = π 2 /6 is

X∞ X∞
1 1
ζ(2) = 2
=3 
i=1
i
i=1
i 2ii
2

∞  i
3 X (1)2i 1
= 3
.
2 ( 2 )i (2)i 4
i=0

A generalization was proved by Herb Wilf using (a variation of)


the WZ method.
This identity is a special case (x = 0) of the
Bailey-Borwein-Bradley formula

X ∞
X
2n 1
ζ(2n + 2)x =
i2 − x2
n=0 i=1
This identity is a special case (x = 0) of the
Bailey-Borwein-Bradley formula

X ∞
X
2n 1
ζ(2n + 2)x =
i2 − x2
n=0 i=1

X i−1
Y
1 4x 2 − m2
=3 2i

2 2
i (i − x ) m=1
x 2 − m2
i=1
This identity is a special case (x = 0) of the
Bailey-Borwein-Bradley formula

X ∞
X
2n 1
ζ(2n + 2)x =
i2 − x2
n=0 i=1

X i−1
Y
1 4x 2 − m2
=3 2i

2 2
i (i − x ) m=1
x 2 − m2
i=1
∞  
3/2 X (2)i (1 − 2x)i (1 + 2x)i 1 i
= .
1 − x2 ( 32 )i (2 − x)i (2 + x)i 4
i=0
This identity is a special case (x = 0) of the
Bailey-Borwein-Bradley formula

X ∞
X
2n 1
ζ(2n + 2)x =
i2 − x2
n=0 i=1

X i−1
Y
1 4x 2 − m2
=3 2i

2 2
i (i − x ) m=1
x 2 − m2
i=1
∞  
3/2 X (2)i (1 − 2x)i (1 + 2x)i 1 i
= .
1 − x2 ( 32 )i (2 − x)i (2 + x)i 4
i=0

Proved using a WZ pair by Khodabakhsh and Tatiana Hessami


Pilehrood.
We will see that their WZ pair comes from the WZ form for the
Chu-Vandermonde theorem, or equivalently Gauss’s theorem,
which is
X∞
(a)i (b)i Γ(c)Γ(c − a − b)
= .
(1)i (c)i Γ(c − a)Γ(c − b)
i=0

It is convenient to write this in the form



X (k )i (l)i Γ(j)Γ(j + k + l)
=
(1)i (j + k + l)i Γ(j + k )Γ(j + l)
i=0

which corresponds to the nicely symmetric WZ form


 
Γ(i + k )Γ(i + l)Γ(j + k )Γ(j + l) δi δj δk δl
+ + +
Γ(i)Γ(j)Γ(k )Γ(l)Γ(i + j + k + l) i j k l
We have

X ∞
X 1
ζ(2n + 2)x 2n =
i2 − x2
n=0 i=1

X 1
=
(i + 1)2 − x 2
i=0

X 1
=
(1 + x + i)(1 − x + i)
i=0

1 X (1 + x)i (1 − x)i
= .
1 − x2 (2 + x)i (2 − x)i
i=0
We want to transform the summand of Gauss’s theorem,
(k )i (l)i
(1)i (j + k + l)i

into a constant times


(1 + x)i (1 − x)i
.
(2 + x)i (2 − x)i
We want to transform the summand of Gauss’s theorem,
(k )i (l)i
(1)i (j + k + l)i

into a constant times


(1 + x)i (1 − x)i
.
(2 + x)i (2 − x)i

If we replace i by 1 + x + i in (k )i (l)i /(1)i (j + k + l))i (shifting)


and then set j = 1, k = 0, l = −2 we get

2x (1 + x)i (1 − x)i
− 2
·
Γ(0)(1 − x ) (2 + x)i (2 − x)i
We want to transform the summand of Gauss’s theorem,
(k )i (l)i
(1)i (j + k + l)i

into a constant times


(1 + x)i (1 − x)i
.
(2 + x)i (2 − x)i

If we replace i by 1 + x + i in (k )i (l)i /(1)i (j + k + l))i (shifting)


and then set j = 1, k = 0, l = −2 we get

2x (1 + x)i (1 − x)i
− 2
·
Γ(0)(1 − x ) (2 + x)i (2 − x)i

We can get rid of the Γ(0) in the denominator by shadowing.


The shadowed WZ form is

Γ(i + k ) Γ(i + l) Γ(j + k ) Γ(j + l) Γ(1 − k )


ω = (−1)k
Γ(i) Γ(j) Γ(l) Γ(i + j + k + l)
 
δi δj δk δl
× + + +
i j k l

If we sum ω in the direction (1, 0, 0, 0) starting at the point


(1 + x, 1, 0, −2x) we get

X X ∞
1 1
−2x 2 2
= −2x .
(1 + i) − x i − x2
2
i=0 i=1
The shadowed WZ form is

Γ(i + k ) Γ(i + l) Γ(j + k ) Γ(j + l) Γ(1 − k )


ω = (−1)k
Γ(i) Γ(j) Γ(l) Γ(i + j + k + l)
 
δi δj δk δl
× + + +
i j k l

If we sum ω in the direction (1, 0, 0, 0) starting at the point


(1 + x, 1, 0, −2x) we get

X X ∞
1 1
−2x 2 2
= −2x .
(1 + i) − x i − x2
2
i=0 i=1

To transform the sum, we compute the value of the ith step


starting at the same point and going in another direction. We
look for something interesting and we have to check that the
sum along the “connecting path" goes to 0.
We find that the direction (1, 2, −1, −1) gives us what we want:
the sum starting at (1 + x, 1, 0, −2x) gives
∞  
3x X (2)n (1 − 2x)n (1 + 2x)n 1 n
− .
1 − x2 ( 32 )n (2 − x)n (2 + x)n 4
n=0
We find that the direction (1, 2, −1, −1) gives us what we want:
the sum starting at (1 + x, 1, 0, −2x) gives
∞  
3x X (2)n (1 − 2x)n (1 + 2x)n 1 n
− .
1 − x2 ( 32 )n (2 − x)n (2 + x)n 4
n=0

An advantage of this approach is that it gives us something


more; if we start at the point (x, 1, 0, y − x) we get the more
general formula


X 1
(i + x)(i + y )
i=0

1 X
= (1 + x + y + 3i)
2xy
i=0
 i
i! (1 + x − y )i (1 + y − x)i 1
× .
( 32 )i (1 + x)i (1 + y )i 4
Amalgamated forms of identities
Recall that the coefficients of the variables in a WZ form must
be integers.
We have the identity

(d)2i = 22i ( 12 d)i ( 21 d + 12 )i


Amalgamated forms of identities
Recall that the coefficients of the variables in a WZ form must
be integers.
We have the identity

(d)2i = 22i ( 12 d)i ( 21 d + 12 )i

So in Gauss’s theorem

X (a)i (b)i Γ(c)Γ(c − a − b)
= .
(1)i (c)i Γ(c − a)Γ(c − b)
i=0

we can set a = d/2, b = d/2 + 1/2 and simplify to get



X (d)2i −2i 22c−d−2 Γ(c)Γ(c − d − 12 )
2 = √
(1)i (c)i πΓ(2c − d − 1)
i=0
We can get a corresponding WZ form
√  
21−2i−2j−k π Γ(2i + k )Γ(2j + k ) δi δj δk
+ −2
Γ(i)Γ(j)Γ(k )Γ(i + j + k + 12 ) i j k
We can get a corresponding WZ form
√  
21−2i−2j−k π Γ(2i + k )Γ(2j + k ) δi δj δk
+ −2
Γ(i)Γ(j)Γ(k )Γ(i + j + k + 12 ) i j k

Is it possible to derive this directly from the WZ form for the


general Gauss’s theorem without a separate application of
Gosper’s algorithm?
Sporadic WZ forms

There are many evaluations of 2 F1 ’s with just one free


parameter. They all have WZ pairs, but these seem to be
sporadic.

You might also like